1991
DOI: 10.1029/90wr02762
|View full text |Cite
|
Sign up to set email alerts
|

Distance of movement of coarse particles in gravel bed streams

Abstract: Distributions of distance of bedload particle movement were examined in two gravel bed streams using several hundred magnetically tagged cobbles and pebbles. The compound Poisson model of Einstein-Hubbell-Sayre and a simple gamma function model were compared with observed distributions of moved particles, and of all particles. Both models fit the data reasonably well for small mean displacements, but notable misfits occurred in an event with large mean displacement. When mean particle travel distance approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
175
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(193 citation statements)
references
References 6 publications
17
175
0
1
Order By: Relevance
“…The mean transport distance is the coefficient l D which we assume is inversely proportional to grain size [Hassan and Church, 1991],…”
Section: A2 Power Law Pdfs Via Mixing Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean transport distance is the coefficient l D which we assume is inversely proportional to grain size [Hassan and Church, 1991],…”
Section: A2 Power Law Pdfs Via Mixing Distributionsmentioning
confidence: 99%
“…In reality, grains of bed sediment of variable mass are transported with a broad range of particle velocities over a wide range of distances by numerous flood discharges of varying magnitude [Stark et al, 2000]. Although the composite, long-term probability distribution of transport distances is not yet known empirically, studies such as those of Hassan and Church [1991] and Church and Hassan [1992] have recorded semiheavy (exponential or gamma) probability density functions (pdfs) of particle transport distances after one or two floods, and on theoretical grounds it is reasonable to deduce that it is heavy tailed. Probability distributions with heavy, power law tails arise in nature for one of (at least) three reasons: (1) because the governing process is self-similar, (2) through the mixing of distributions of constituent properties (Appendix A2), or (3) through summation of quantities with arbitary shape, broad-tailed distributions and convergence to a stable law pdf according to the Lévy limit theorem [Lévy, 1937;Feller, 1971].…”
Section: Introductionmentioning
confidence: 99%
“…The application of passive tracer particles has taken various forms, such as exotic lithologies (Houbrechts et al, 2011), painted bed material (Wilcock, 1997b), magnetic (Hassan et al, 1991), radioactive (Sayre and Hubbell, 1965;Bradley et al, 2010), and RFID (Lamarre et al, 2005;Bradley and Tucker, 2012;Phillips et al, 2013;Schneider et al, 2014). A benefit of RFID-equipped tracer particles is that each particle is uniquely identified, which allows its position to be measured at longer timescales with high recovery rates (Bradley and Tucker, 2012;Phillips et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Available data suggest that particle step lengths at the intermediate scale (i.e., distances between long rests) are likely to follow exponential [7,8,13], gamma [12], or two-parameter gamma [11] distributions. In these references, it can also be found that the mean step lengths may vary, depending on travel conditions, from 100 to 150 particle diameters.…”
Section: Introductionmentioning
confidence: 99%